Endovascular treatment of abdominal aortic aneurysms. Issue 6 (June 2018) - Thomas, Matthew; Wyatt, Mike
Abstract: The management of abdominal aortic aneurysms has been revolutionized by the development of endovascular stent grafts. The deployment of these devices requires precise clinical and endovascular skills. This review aims to provide an overview of the essential aspects of an endovascular repair of an abdominal aortic aneurysm (EVAR), from initial presentation and assessment for the procedure through to follow-up and long-term outcomes. Consideration is also given to the newer devices, e.g. fenestrated and branched stent grafts, which have further expanded the numbers of patients who are suitable for treatment by EVAR. Abdominal aortic aneurysm etiology, screening and open repair is dealt with in the previous article.